Anti-sintering in-situ desolventizing platinum-based LaFeO3 catalyst and preparation method thereof
By achieving perfect solid solution of platinum-based LaFeO3 catalyst and the formation of Pt nanoparticles during the muffle furnace calcination process, the problem of sintering and activity of supported metal catalysts under high temperature conditions is solved, and the long life and efficient activity of the catalyst are achieved , reducing production costs and environmental pollution.
Patent Information
- Application Number
- CN202411592541.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
Supported metal catalysts are prone to sintering and metal leaching under high temperature conditions, resulting in a decrease in catalyst activity, increasing production costs and causing environmental pollution.
By taking simple insulation measures at the low temperature stage during the muffle furnace calcination process, the perfect solid solution of the platinum-based LaFeO3 catalyst is achieved, the agglomeration of precious metal Pt on the perovskite surface is avoided, and the reduction treatment is carried out by 5% H2/95% Ar 1-2 nm Pt nanoparticles are formed.
It significantly extends the service life of the catalyst, maintains the catalytic activity under high temperature conditions, reduces production costs, and reduces environmental pollution.
Smart Images

Figure CN119425727A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature durable anti-sintering of catalysts, and particularly relates to an anti-sintering in-situ desolvation platinum-based LaFeO3 catalyst and a preparation method and application thereof. Background Art
[0002] Supported metal catalysts are widely used in many fields such as chemical production, clean energy development and photocatalytic reactions. However, such catalysts often face the problem of decreased activity due to high-temperature sintering and metal leaching during use. This not only affects the performance of the catalyst, but also leads to expensive regeneration costs. For example, the deactivation of the catalyst may lead to reduced production efficiency and increased energy consumption, thereby indirectly increasing production costs, seriously affecting the profitability and market competitiveness of the enterprise. Studies have pointed out that the economic losses caused by catalyst failure can reach millions of dollars, especially in large-scale chemical production. In addition, since deactivated catalysts need to be frequently replaced and regenerated, it causes waste of raw materials and environmental pollution, further increasing the ecological burden. Therefore, a deep understanding of the mechanism of catalyst sintering is crucial to the design of durable catalysts.
[0003] Ostwald ripening and migration-coalescence are the two main mechanisms that lead to the sintering and aggregation of metal nanoparticles, and these two mechanisms often act alternately in the agglomeration process of the catalyst. In-depth research on the sintering mechanism of metal nanoparticles has prompted scientists to explore new solutions to develop more stable metal nanoparticle catalysts. For example, the method of coating metal nanoparticles with oxides or carbon layers can effectively reduce the sintering of metals, but this method sometimes blocks some active sites, resulting in a decrease in catalyst activity. Therefore, it is urgent to develop new sintering-resistant catalysts to meet the above challenges and achieve long-term stable catalytic performance under high temperature conditions.
[0004] The application of perovskite oxides in the field of catalysis has attracted more and more attention, especially the regulation of their catalytic performance by means of A-site or B-site doping and dissolution of B-site elements. The dissolution of B-site elements is an important means to regulate catalytic performance, especially in redox reactions. By controlling the reaction conditions (such as temperature, atmosphere, etc.), the B-site metal can be partially dissolved to form nanometal particles, which can play an important role in catalytic reactions. Different B-site elements have different redox properties and catalytic activities. Selecting the right B-site element can significantly improve the catalytic performance. By adjusting the composition and structure of perovskite, the type and density of dissolved metal particles can be controlled. For example, by adjusting the reaction atmosphere, temperature and reaction time, the morphology and distribution of nanometal particles can be precisely controlled, thereby optimizing the catalytic performance. Perovskite oxide catalysts show excellent catalytic activity in a variety of reactions, such as oxygen reduction, hydrogenation and CO oxidation. By rationally designing and adjusting their structure, efficient and highly selective catalytic reactions can be achieved.
[0005] In recent years, many researchers have devoted themselves to developing new perovskite-noble metal composite catalysts to improve catalytic performance. By adjusting the synthesis conditions and optimizing the material composition and structure, effective control of Pt particles can be achieved, thereby improving the overall performance of the catalyst. In the noble metal catalysts with perovskite structure, noble metals such as Pt are prone to agglomeration during the synthesis process, especially under high temperature conditions. During the heating process, the increase in the thermal energy of Pt will lead to increased mobility of its atoms, resulting in agglomeration to form larger particles. This agglomeration phenomenon not only reduces the specific surface area of Pt, but may also affect its catalytic activity, because the catalytic activity is usually related to the size of metal nanoparticles, and larger particles tend to have lower catalytic activity. Agglomerated Pt particles are also unable to effectively combine with perovskite, resulting in a decrease in the overall performance of the catalyst. The interaction between Pt and perovskite is crucial to the stability and activity of the catalyst.
[0006] Kothari M, Jeon Y, Miller DN, et al. Platinum incorporation intotitanate perovskites to deliver emergent active and stable platinumnanoparticles[J]. Nature Chemistry, 2021, 13(7): 677-682. proposed to use a solid-phase method to form a "Trojan horse" with Pt and rare earth elements to inhibit the agglomeration of Pt during calcination. However, this method requires very high temperatures and is time-consuming and labor-intensive, and cannot be applied to the calcination of ordinary catalysts.
[0007] Therefore, in view of the above difficulties, it is particularly important to develop efficient and economical new catalysts, especially those that are resistant to high temperatures and sintering and have good catalytic performance.
[0008] In this context, this patent proposes a high-temperature, durable, sintering-resistant in-situ desolvated platinum-based LaFeO3 catalyst and its preparation method, aiming to improve the stability and activity of the catalyst in a high-temperature environment while reducing the difficulty of catalyst preparation to promote its promotion and development in industrial applications. Summary of the invention
[0009] In view of the above problems, an object of the present invention is to provide a sintering-resistant in-situ desolvation platinum-based LaFeO3 catalyst and a preparation method thereof, and a precious metal catalyst that can achieve efficient removal of carbon and hydrogen.
[0010] Another object of the present invention is to provide a simple and efficient method for preparing the above-mentioned in-situ precipitation platinum-based LaFeO3 catalyst.
[0011] The present invention uses simple heat preservation measures in the low temperature stage without changing the final calcination temperature during the muffle furnace calcination process, thereby obtaining a perfectly solid-dissolved platinum-based LaFeO3 catalyst. That is, Pt is perfectly integrated into the LaFeO3 perovskite structure during the low-temperature calcination process to form LaFe 0.95 Pt 0.05 O3 structure, thereby preventing Pt from agglomerating on the LaFeO3 surface during normal heating to form Pt x / LaFe 0.95 Pt 0.05-x O3.
[0012] The catalyst is obtained by perfect solid dissolution of Pt in the LaFeO3 perovskite structure. 0.95 Pt 0.05 O3 structure, 5% H2 / 95% Ar was introduced into the tube furnace and the temperature was increased for reduction treatment. The sample after 5% H2 / 95% Ar treatment is called desolvated LaFe 0.95 Pt 0.05 The purpose of O3.5% H2 / 95% Ar treatment is to make LaFe 0.95 Pt 0.05 The Pt inside the O3 structure is treated in a reducing atmosphere to form Pt particles with a particle size of 1-2 nm on the surface of the perovskite.
[0013] The desolvated catalyst obtained by the above 5% H2 / 95% Ar reduction treatment can achieve the initial activity after 100 hours of air flow during the high-temperature heat treatment at 800°C. Therefore, compared with ordinary catalysts, the catalyst activity life is greatly increased.
[0014] In order to achieve the above object, the specific technical solution adopted by the present invention is as follows: A sintering-resistant in-situ desolvation platinum-based LaFeO3 catalyst, comprising a precious metal Pt perfectly dissolved in a perovskite structure, characterized in that the precious metal Pt is perfectly dissolved in the perovskite structure, avoiding the agglomeration of the precious metal Pt on the perovskite surface, that is, the precious metal Pt is completely dissolved in the perovskite structure to form LaFe 0.95 Pt 0.05 O3 instead of Pt x / LaFe 0.95 Pt 0.05-x O3. After hydrogen treatment, the outer surface can evenly distribute high-performance catalysts with platinum particles of 1-2 nm in size.
[0015] A method for preparing a sintering-resistant in-situ desolvation platinum-based LaFeO3 catalyst, characterized in that it comprises the following steps: (1) Preparation of precursor solution: Weigh appropriate amounts of lanthanum salt, iron salt and platinum salt, add appropriate amounts of chelating agent, and stir at room temperature until completely dissolved to form a solution; (2) Preparation of a gel-like substance: placing the precursor solution obtained in step (1) on a heated stirring table for heating and stirring to finally obtain a gel-like substance; (3) Preparation of a dry gel-like substance: placing the gel-like substance obtained in step (2) in an oven for high-temperature drying to obtain a dry gel-like substance; (4) Preparation of platinum-based perovskite catalyst: After grinding the dried gel-like substance obtained in step (3), weighing an appropriate amount of sample and placing it in a muffle furnace for heating and calcining; (5) Desolventization treatment of platinum-based perovskite catalyst: Weigh an appropriate amount of the catalyst sample obtained in step (4) and place it in a tube furnace, introduce gas, and perform temperature reduction treatment. Finally, the catalyst is prepared.
[0016] Furthermore, in the above step (1), the salt is lanthanum nitrate hexahydrate with a purity of 99.99%, the iron salt is ferric nitrate nonahydrate with a purity of 99.99%, and the platinum salt is platinum nitrate with a purity of 18.02%. The chelating agent is citric acid with a purity of 99.99%. The molar ratio of lanthanum nitrate hexahydrate, ferric nitrate nonahydrate, platinum nitrate and citric acid is 1:0.95:0.05:2.4.
[0017] Furthermore, in the above step (1), the solvent is deionized water.
[0018] Furthermore, in the above step (2), the heating and stirring temperature is 80°C.
[0019] Furthermore, in the above step (3), the oven drying temperature is 110°C and the drying time is 24 h.
[0020] Furthermore, in the above step (4), the calcination conditions are: heating to 200°C at 2°C / min at room temperature, keeping at 200°C for 30 min, then heating to 500°C at 5°C / min, keeping at 500°C for 60 min, and after the keeping, heating to 800°C at 5°C / min, and keeping at 800°C for 120 min.
[0021] Furthermore, in the above step (5), the gas introduced into the tube furnace is: 5% H2 / 95% Ar. The calcination conditions are: heating from room temperature to 700°C at 5°C / min, and keeping at 700°C for 120 min.
[0022] The beneficial effects of the present invention are as follows: the noble metal Pt does not form Pt agglomerates during the calcination process of the catalyst preparation, thereby increasing the number of Pt active sites and significantly extending the service life of the catalyst. Therefore, the cost is greatly reduced compared with the normally heated Pt-based catalyst and the commercial platinum-based catalyst; the LaFe 0.95 Pt 0.05 O3 catalyst has extremely strong catalytic activity. In the presence of this catalyst, in a simulated high-temperature heat treatment atmosphere, even at a temperature of up to 800°C for 100 hours, it still maintains its initial activity, which has great application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The non-precipitated XRD diagrams of Example 1 of the present invention and Comparative Examples 1 and 2 are shown.
[0024] Figure 2 These are the Raman images of Example 1 of the present invention and Comparative Examples 1 and 2 without desolvation.
[0025] Figure 3 The non-desolvated CO-IR infrared adsorption diagrams of Example 1 and Comparative Examples 1 and 2 of the present invention are shown.
[0026] Figure 4 TEM images of Example 1 of the present invention before and after desolvation.
[0027] Figure 5 TEM images of comparative example 1 of the present invention without desolvation and with desolvation.
[0028] Figure 6 These are the SEM and Mapping electron microscope images of Example 1 of the present invention before and after aging.
[0029] Figure 7 These are the SEM and Mapping electron microscope images of Comparative Example 1 of the present invention before and after aging.
[0030] Figure 8 These are TEM images of comparative example 3 of the present invention before and after aging.
[0031] Fig. 9 It is a comparison chart of the conversion rate of undesolvated C3H6 of Example 1 of the present invention and Comparative Example 1.
[0032] Fig.10 It is a comparison chart of the desolventizing and aging C3H6 conversion rates of Example 1 of the present invention and Comparative Examples 1 and 3.
[0033] Fig.11 Schematic diagram of hydrogen treatment and aging of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described below in combination with comparative examples and drawings and through specific embodiments, but the protection scope of the present invention should not be limited thereto. Embodiment 1:
[0035] Dissolve 0.866 g of lanthanum nitrate hexahydrate, 0.7676 g of ferric nitrate nonahydrate, 0.1082 g of platinum nitrate solution and 0.9221 g of citric acid in 20 ml of deionized water and stir at room temperature until completely dissolved. Place the obtained solution on a heated stirring table for heating and stirring at 80°C. Place the sol-gel sample obtained after heating and stirring in a 110°C oven and dry for 24 h.
[0036] The dried sample was fully ground in a mortar, and then an appropriate amount of the ground sample was weighed and heated to 200°C at 2°C / min in a muffle furnace at room temperature, kept at 200°C for 30 min, then continued to heat to 500°C at 5°C / min, kept at 500°C for 60 min, and continued to heat to 800°C at 5°C / min after the end of the heat preservation, and kept at 800°C for 120 min. 0.95 Pt 0.05 O3 catalyst. The Pt loading in this catalyst is 3.9%.
[0037] Figure 1 Example 1 did not dissolve LaFe 0.95 Pt 0.05 The XRD spectrum of the O3 catalyst shows that the LaFeO3 crystal structure has not been changed after calcination at a low temperature stage.
[0038] Figure 2 Example 1 did not dissolve LaFe 0.95 Pt 0.05 The Raman spectrum of O3 catalyst was obtained by using an argon ion laser with a wavelength of 532 nm as the excitation source. Figure 2 It can be seen that Example 1 has a -1 The Raman peak signal is very strong at the position of Pt, which can be attributed to the contribution of oxygen vacancies. + / 4 + , and the Pt atomic radius is greater than the Fe atomic radius, so no matter what valence state Pt combines with lanthanum ferrite, oxygen vacancies will be generated inside the catalyst. Figure 2 It can be seen that the solid solubility degree of Pt in Example 1 is greater than that of other comparative samples.
[0039] Figure 3 The middle is the LaFe without desolventizing in Example 1 0.95 Pt 0.05 The CO-IR spectrum of the O3 catalyst obtained by measuring CO chemical adsorption on the Auto Chem II 2920 chemical adsorption instrument. From the relevant knowledge of CO-IR spectrum, it can be known that if Pt exists on the surface, 2080 cm -1 -2100 cm -1 The infrared adsorption signal of CO should be shown in the range Figure 3 It can be shown that there is no Pt on the surface of the non-desolvated sample in Example 1.
[0040] The undesolvated catalyst was placed in a tube furnace, 5% H2 / 95% Ar was introduced into the tube furnace, and the temperature was raised to 700℃ at 5℃ / min for 2 h to finally obtain the desolvated LaFe 0.95 Pt 0.05 O3 catalyst.
[0041] Figure 4 Example 1 without desolventizing LaFe 0.95 Pt 0.05 O3 and Desolvation of LaFe 0.95 Pt 0.05 TEM morphology comparison of O3 catalyst. From the TEM data, it can be seen that no Pt was observed on the surface of Example 1 before desolventization. After hydrogen desolventization, a large number of Pt nanoparticles were observed on the surface of the desolventized sample of Example 1, with a particle size of 1-2 nm. Figure 4 TEM data show that in Example 1, only after hydrogen desolvation treatment will Pt emerge from the interior of the crystal structure to the surface.
[0042] The desolvated catalyst was placed in a tube furnace, air was introduced into the tube furnace, and the temperature was raised to 800°C for 100 hours to obtain aged LaFe 0.95 Pt 0.05 O3 catalyst.
[0043] Figure 7 The SEM and mapping electron microscope images of Example 1 after desolventizing and aging are shown. Figure 7 SEM and Mapping show that Pt particles evenly emerge on the surface of Example 1 after desolventizing and aging, and no Pt agglomeration occurs.
[0044] The three samples of the prepared catalyst, namely, the undesolvated, desolvated and aged catalyst, were subjected to laboratory simulation gas distribution evaluation. The samples used in the evaluation process were a mixture of catalyst and quartz sand at a weight ratio of 100 mg:300 mg. The mixed samples were placed in a quartz reaction tube with a diameter of 10 mm. The test reaction atmosphere was 335 ml / min N2, 125 ml / min Air, 40 ml / min C3H6 (space velocity 100000 h -1 ), the heating rate was 5°C / min. During the reaction, the temperature of the electric furnace was controlled by a temperature controller, and the concentration of CO2 generated during the reaction was measured by an infrared spectrometer.
[0045] The conversion rate of the undesolvated sample in Example 1 to C3H6 reaction is obtained as follows: Fig. 9 As shown. It can be seen that since there is no precious metal Pt on the surface of the sample of Example 1 without desolventizing, the catalytic combustion performance is the worst, catalyzing the C3H6 reaction T 50 It is 470℃.
[0046] The conversion rates of the desolventized sample and the aged sample of Example 1 for the reaction of C3H6 are obtained as follows: Fig.10 As shown. It can be seen that since Pt in Example 1 sample is perfectly dissolved in the perovskite lattice to form LaFe 0.95 Pt 0.05 O3, so Pt did not agglomerate during the aging process, so the desolventized catalytic combustion performance of Example 1 was not much different from the aging catalytic combustion performance of Example 1. T 50 Both are 225℃.
[0047] Fig.11 Schematic diagram of hydrogen treatment and aging in Example 1. Comparative Example 1:
[0048] The method of this comparative example is basically the same as that of Example 1, except that the calcination process of Example 1 is changed.
[0049] In air, the temperature was raised from room temperature to 200°C at 2°C / min, kept at 200°C for 30 min, then further raised to 800°C at 5°C / min, and kept at 800°C for 120 min. x / LaFe 0.95 Pt 0.05-x O3 is not desolvated catalyst. The Pt loading in this catalyst is 3.9%.
[0050] Figure 1 Comparative Example 1 did not desolventize Pt x / LaFe 0.95 Pt 0.05-x The XRD spectrum of O3 catalyst shows that the sample calcined at normal temperature has the LaFeO3 crystal structure.
[0051] Figure 2 Comparative Example 1 did not desolventize Pt x / LaFe 0.95 Pt 0.05-x The Raman spectrum of O3 catalyst was obtained by using an argon ion laser with a wavelength of 532 nm as the excitation source. Figure 2 It can be seen that the comparative example 1 at 660 cm -1 There is no strong Raman peak signal at the place, which shows that there are only a small amount of oxygen vacancies in the sample of Comparative Example 1, so only a small amount of Pt is integrated into the LaFeO3 crystal structure.
[0052] Figure 3 Comparative Example 1 is a case where Pt is not desolvated. x / LaFe 0.95 Pt 0.05-x The CO-IR spectrum of the O3 catalyst obtained by measuring CO chemical adsorption on the Auto Chem II 2920 chemical adsorption instrument. From the relevant knowledge of CO-IR spectrum, it can be known that if Pt exists on the surface, 2080 cm -1 -2100 cm -1 The infrared adsorption signal of CO should be shown in the range. Figure 3 In the comparative example 1, a strong CO infrared adsorption peak is shown in the above range, thus indicating that there is detectable Pt on the surface of the non-desolvated sample in the comparative example 1.
[0053] The undesolvated catalyst was then placed in a tube furnace, 5% H2 / 95% Ar was introduced into the tube furnace, and the temperature was raised to 700 °C for 2 h to finally obtain the desolvated Pt x / LaFe 0.95 Pt 0.05-x O3 catalyst.
[0054] Figure 5 Comparative Example 1: Pt was not desolvatedx / LaFe 0.95 Pt 0.05-x O3 and Pt desolvation x / LaFe 0.95 Pt 0.05-x TEM morphology comparison of O3 catalyst. From the TEM data, it can be seen that Pt can be observed on the surface of Comparative Example 1 before desolventization, with a particle size of 4-5 nm. After hydrogen desolventization, Pt nanoparticles are also observed on the surface of the desolventized sample of Comparative Example 1, with a particle size of 1-2 nm.
[0055] The desolvated catalyst was placed in a tube furnace, air was introduced into the tube furnace, and the temperature was raised to 800°C for 100 hours to finally obtain aged Pt x / LaFe 0.95 Pt 0.05-x O3 catalyst.
[0056] Figure 7 The SEM and Mapping electron microscope images of comparative example 1 after desolventizing and aging. Figure 7 SEM and Mapping show that agglomerated Pt particles appear on the surface of Comparative Example 1 after desolventizing, that is, Pt that has not been dissolved into the LaFeO3 crystal structure during the calcination process agglomerates during the normal heating process, and the Pt particle size is 300 nm. The size and number of Pt particles on the surface of Comparative Example 1 after aging are larger than those of the desolventized sample before aging, that is, the Pt that has not been dissolved into the crystal structure during the aging process of Comparative Example 1 has been affected by high temperature and oxidation, and the sintering of precious metals has occurred on the sample surface, and the Pt particle size has increased to the micron level.
[0057] The conversion rate of the undesolventized sample of Comparative Example 1 to C3H6 reaction is obtained as follows: Fig. 9 As shown. It can be seen that due to the presence of precious metal Pt on the surface of the sample of comparative example 1 without desolventization, the catalytic combustion performance is the best, catalyzing the C3H6 reaction T 50 It is 270℃.
[0058] The conversion rates of the desolventized sample in comparative example 1 and the aged sample in comparative example 1 for C3H6 reaction are obtained as follows: Fig.10 As shown. It can be seen that since Pt did not completely enter the lattice during the calcination process of the sample in Comparative Example 1, Pt agglomerates during the aging process. Therefore, the desolventized catalytic combustion performance of Comparative Example 1 is stronger than the aging catalytic combustion performance of Comparative Example 1. T 50 is 225℃, while the aging catalytic combustion of comparative example 1 T 50 is 260℃.
[0059] Fig.11 Schematic diagram of hydrogen treatment and aging of Comparative Example 1. Comparative Example 2:
[0060] The method of this comparative example is basically the same as that of comparative example 1, except that the material composition ratio of comparative example 1 is changed.
[0061] Dissolve 0.866 g of lanthanum nitrate hexahydrate, 0.808 g of ferric nitrate nonahydrate, and 0.9221 g of citric acid in 20 ml of deionized water and stir at room temperature until completely dissolved. Place the resulting solution on a heated stirring table for heating and stirring at 80°C. Place the resulting sol-gel sample in a 110°C oven and dry for 24 h.
[0062] The sample obtained after drying was fully ground in a mortar, and then an appropriate amount of the ground sample was weighed and heated to 200°C at 2°C / min at room temperature in a muffle furnace, kept at 200°C for 30 min, and then continued to heat to 800°C at 5°C / min, and kept at 800°C for 120 min. After the insulation was completed, LaFeO3 catalyst was obtained.
[0063] Figure 1 Comparative Example 2 is the XRD spectrum of LaFeO3 catalyst, and it can be obtained that the sample calcined at normal temperature has a LaFeO3 crystal structure.
[0064] Figure 2 Comparative Example 2 is a Raman spectrum obtained by using an argon ion laser with a wavelength of 532 nm as the excitation source for LaFeO3 catalyst. Since Comparative Example 2 was not doped with Pt during the calcination process, the Raman spectrum of Comparative Example 3 at 660 cm -1 There is no Raman peak signal.
[0065] Figure 3 Comparative Example 2 is a CO-IR spectrum obtained by measuring CO chemical adsorption of LaFeO3 catalyst in an Auto Chem II 2920 chemical adsorption instrument. From the relevant knowledge of CO-IR spectrum, it can be known that if Pt exists on the surface, 2080 cm -1 -2100cm -1 The infrared adsorption signal of CO should be shown in the range. Figure 3 Since the comparative example 2 was not doped with the Pt element during the calcination process, the CO infrared adsorption peak was not detected in the comparative example 2. Comparative Example 3:
[0066] Comparative Example 3 is a case where the same amount of Pt is impregnated onto commercial γ-Al2O3 using a loading method for comparison with Example 1.
[0067] 0.4329 g of platinum nitrate solution was selected and evenly loaded on 1 g of γ-Al2O3 powder by the equal amount impregnation method while adding dropwise and stirring. The obtained sample was then dried at 110°C in an air atmosphere for 12 hours, taken out and ground into powder, and heated to 500°C at 5°C / min at room temperature in air, and kept at 500°C for 120 min. A Pt / γ-Al2O3 catalyst was obtained. The Pt loading in the catalyst was 3.9%.
[0068] The Pt / γ-Al2O3 catalyst was placed in a tubular furnace, 5% H2 / 95% Ar was introduced into the tubular furnace, and the temperature was raised to 700°C at 5°C / min for 2 h to finally obtain a desolvated Pt / γ-Al2O3 catalyst.
[0069] The desolvated Pt / γ-Al2O3 catalyst was placed in a tubular furnace, Air was introduced into the tubular furnace, and the temperature was raised to 800°C for 100 h to obtain an aged Pt / γ-Al2O3 catalyst.
[0070] Figure 8 TEM images of comparative example 3 after desolventizing and aging. Figure 8 It can be seen that the particle size of the Pt particles before aging in Comparative Example 3 is 3-4 nm. After aging in Comparative Example 3, the Pt particles on the surface undergo severe precious metal sintering, and the particle size of the Pt particles increases to 40-80 nm.
[0071] The conversion rates of the desolventized sample of Comparative Example 3 and the aged sample of Comparative Example 3 for the reaction of C3H6 are obtained as follows: Fig.10 As shown. It can be seen that due to the agglomeration of Pt in the sample of comparative example 3 during the aging process, the desolventized catalytic combustion performance of comparative example 3 is stronger than the aging catalytic combustion performance of comparative example 3. T 50 The aging catalytic combustion of Comparative Example 3 is 230°C. T 50 It is 245℃.
[0072] Fig.11 Schematic diagram of hydrogen treatment and aging for Comparative Example 3.
Claims
1. A sintering-resistant in-situ desolvation platinum-based LaFeO3 catalyst, comprising precious metal platinum perfectly dissolved in a perovskite structure, characterized in that: The precious metal platinum is perfectly dissolved in the perovskite structure, avoiding the agglomeration of the precious metal Pt on the perovskite surface, that is, the precious metal platinum is completely dissolved in the perovskite structure, and the outer surface is evenly distributed with nano-platinum particles after hydrogen treatment. Even if treated for a long time at high temperature, the catalyst still maintains its initial activity.
2. The in-situ desolvation platinum-based LaFeO3 catalyst according to claim 1, characterized in that The precious metal is perfectly dissolved in the perovskite structure, and after hydrogen treatment, the platinum particles that are dissolved to the surface are 2-3 nm.
3. The in-situ desolvation platinum-based LaFeO3 catalyst according to claim 1, characterized in that The synthesis steps are simple and the cost is low.
4. A method for preparing an in-situ desolvation platinum-based LaFeO3 catalyst according to claim 1, characterized in that It includes the following steps: (1) Preparation of precursor: Weigh appropriate amounts of lanthanum salt, iron salt and platinum salt, add appropriate amounts of chelating agent, and stir at room temperature until completely dissolved to form a solution; (2) Preparation of a gel-like substance: placing the precursor solution obtained in step (1) on a heated stirring table for heating and stirring to finally obtain a gel-like substance; (3) Preparation of a dry gel-like substance: placing the gel-like substance obtained in step (2) in an oven for drying to obtain a dry gel-like substance; (4) Preparation of in-situ desolvation platinum-based LaFeO3 catalyst: After grinding the dried gel-like substance obtained in step (3), weigh an appropriate amount of sample and place it in a muffle furnace for heating and calcining; (5) In-situ desolvation platinum-based LaFeO3 catalyst desolvation treatment: Weigh an appropriate amount of the catalyst sample obtained in step (4) and place it in a tube furnace to introduce gas for temperature reduction treatment. Finally, the in-situ desolvation platinum-based LaFeO3 catalyst is prepared; (6) Aging treatment of in-situ desolvation platinum-based LaFeO3 catalyst: Weigh an appropriate amount of the catalyst sample obtained in step (5) and place it in a tube furnace to pass gas for heating treatment to obtain an aged platinum-based LaFeO3 catalyst.
5. The preparation method according to claim 5, characterized in that In step (1), the lanthanum salt is lanthanum nitrate hexahydrate with a purity of 99.99%, the iron salt is ferric nitrate nonahydrate with a purity of 99.99%, and the platinum salt is platinum nitrate solution with a purity of 18.02%. The chelating agent is citric acid with a purity of 99.99%. The molar ratio of lanthanum nitrate hexahydrate, ferric nitrate nonahydrate, platinum nitrate and citric acid is 1:0.95:0.05:2.
4.
6. The preparation method according to claim 5, characterized in that In step (1), the solvent is deionized water, and the room temperature is 25°C. In step (2), the heating and stirring temperature is 80°C. In step (3), the oven drying temperature is 110°C, and the drying time is 24 h.
7. The preparation method according to claim 5, characterized in that In step (4), the calcination conditions are as follows: heating to 200°C at 2°C / min at room temperature, keeping at 200°C for 30 min, then heating to 500°C at 5°C / min, keeping at 500°C for 60 min, and then heating to 800°C at 5°C / min after the end of the keeping, and keeping at 800°C for 120 min.
8. The preparation method according to claim 5, characterized in that In step (5), the gas introduced is: 5% H2 / 95% Ar. The calcination conditions are: heating from room temperature to 700°C at 5°C / min, and keeping at 700°C for 120 min.
9. The preparation method according to claim 6, characterized in that In step (6), the gas introduced is: Air. The calcination conditions are: heating from room temperature to 800°C at 5°C / min, and keeping at 800°C for 100 h.